Single particle contributions to the structure of low-lying states of Cr, Ti, Se, Zr and Nd nuclei via precision g-factor measurements - Benczer-Koller, N.; Kumbartzki, G.; Jakob, G.; Holden, J.; Mertzimekis, T. J.; Speidel, K.-H.; Beausang, C.; Kruecken, R.; McMahan, M.; Macchiavelli, A.; Phair, L.; Lee, I.-Y.; et al. (Rev. Mex. Fis., 1999)
Magnetic dipole and electric quadrupole moments have traditionally been critical in the determination of the microscopic wave functions of particular nuclear states. Measurements on nuclei at high spin and energy, as well as on nuclei in superdeformed states have yielded a wealth of information on their structure. The techniques developed for these measurements are now being extended to the study of nuclei far-from-stability such as those which will be accessible via reactions with radioactive beams. Very precise determinations of the magnetic moments of the 21+ states of Cr, Ti, Zr, Se and Nd isotopes, recently carried out via "projectile excitation", place very tight constraints on existing nuclear models, from single particle calculations in the 1fp shell to extended IBM models, and further highlight the importance of the interplay between single particle and collective excitations across the table of isotopes. The experimental results will be presented and compared with theoretical calculations.
Keywords: Independent particle and collective models; Magnetic moments; Nuclear structure